Antibacterial activity of nanoemulsions based on essential oils compounds against species of xanthomonas that cause citrus canker - da Cruz Silva, Gulherme; de Oliveira Filho, Josemar Golçalves [UNESP]; Ribeiro, Marilene de Mori Morselli; de Souza, Clovis Wesley Oliveira; Ferreira, Marcos David (AMG Transcend Association, 2022)
Citrus canker is a bacterial disease that affects citrus crops, caused by microorganisms of the genus Xanthomonas responsible for great damage to citrus production. In this work, the antimicrobial effect of nanoemulsions based on the major compounds of essential oils (EOs) eugenol, thymol, geraniol and menthone were investigated against two strains of Xanthomonas that cause citrus canker (Xac and XauB). Nanoemulsions were produced for each compound using two different stirring speeds (7,000 and 12,000 rpm). All nanoemulsions underwent analysis to characterize particle sizes and stability. Thymol nanoemulsions had the smallest particle sizes (59.8 to 73.9 nm) and the highest stability and also showed the ability to inhibit the development of both strains of bacteria, with minimum inhibitory concentrations (MIC) of 0.03% (v/v), along with eugenol (0.03% (v/v) for Xac and 0.02% (v/v) for XauB) and geraniol nanoemulsions (0.06% (v/v) for both bacteria). Thymol was the compound with the highest minimum bactericidal concentrations (MBC), with values of 0.03% (v/v) for both bacterial strains. Eugenol showed MBC only against XauB, at a concentration of 0.03% (v/v). Geraniol did not show bactericidal activity, suggesting a bacteriostatic action of this compound with the tested microorganisms. In general, the antimicrobial activity of the nanoemulsions was increased with increased agitation speed, particle reduction and greater stability. Therefore, nanoemulsification can be an alternative to applying the antimicrobial activity of natural compounds in the control of citrus canker.
Keywords: Citrus canker; Eugenol; Thymol; Xanthomonas citri subsp. citri; Xanthomonas fuscans subsp. aurantifolii type B